2021
DOI: 10.3390/brainsci11050656
|View full text |Cite
|
Sign up to set email alerts
|

A Network Analysis of the Relationship among Reading, Spelling and Maths Skills

Abstract: Background. Skill learning (e.g., reading, spelling and maths) has been predominantly treated separately in the neuropsychological literature. However, skills (as well as their corresponding deficits), tend to partially overlap. We recently proposed a multi-level model of learning skills (based on the distinction among competence, performance, and acquisition) as a framework to provide a unitary account of these learning skills. In the present study, we examined the performance of an unselected group of third-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Studies show that mathematical and literacy attainment at the age of 7 is a strong predictor of socio‐economic status by the age of 42 as well as academic motivation and duration of education, with these relationships extending beyond factors such as general intelligence or socio‐economic status at birth (Ritchie & Bates, 2013 ). Though the processes underlying learning and performance in mathematics are generally treated separately from those of literacy (Carreiras et al, 2015 ; Zoccolotti et al, 2021 ), research shows that effects of bullying can still be inhibitory to both. Looking at longitudinal evidence, Smith and Skrbiš ( 2016 ) analysed data from the Social Futures and Life Pathways (‘Our Lives’) project and found that bullying was negatively associated with educational attainment when leaving school.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that mathematical and literacy attainment at the age of 7 is a strong predictor of socio‐economic status by the age of 42 as well as academic motivation and duration of education, with these relationships extending beyond factors such as general intelligence or socio‐economic status at birth (Ritchie & Bates, 2013 ). Though the processes underlying learning and performance in mathematics are generally treated separately from those of literacy (Carreiras et al, 2015 ; Zoccolotti et al, 2021 ), research shows that effects of bullying can still be inhibitory to both. Looking at longitudinal evidence, Smith and Skrbiš ( 2016 ) analysed data from the Social Futures and Life Pathways (‘Our Lives’) project and found that bullying was negatively associated with educational attainment when leaving school.…”
Section: Introductionmentioning
confidence: 99%
“…Networks are transdisciplinary and in psychology have been somewhat classical to model personality, psychopathology and attitudes ( Cramer et al, 2012 ; Schmittmann et al, 2013 ; Costantini et al, 2015 , 2017 ; Dalege et al, 2016 ; Borsboom, 2017 ). More recently, networks have been used to characterize neuropsychological performances in adults ( Tosi et al, 2020 ; Ferguson and Alzheimer’s Disease Neuroimaging Initiative, 2021 ) and to understand the relationship among math, reading and spelling skills in children ( Zoccolotti et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…We recently obtained further evidence along these lines in a study in which we examined performance on standard clinical instruments in a sample of typically developing children and used the network analysis to obtain a unitary picture of reading, spelling, and math skills [ 62 ]. The network analysis indicated that the different measures of the same ability (i.e., reading, spelling, and math) formed separate clusters, in keeping with the idea that they are at least in part related to separate competences.…”
Section: Interpretations Of Surface Dyslexia In Acquired and Developmental Casesmentioning
confidence: 99%